INSTITUTIONS OF SECONDARY EDUCATION IN KATERINOSLAV PROVINCE IN THE EARLY XXth CENTURY AND LEARNING FEATURES (Cases of Katerinoslav male gymnasium and Mariupol Mariinsky female gymnasium) - Alina Papats (Cхід, 2020)
Relevance of the article is due to the need to present valuable experience of private and public education gained by educational institutions that were on the territory of modern Ukraine in the early 20th century. The number of students of Katerinoslav male gymnasium and Mariupol Mariinsky female gymnasium in the early 20th century is analyzed in the article. The features of their education in these secondary education institutions are revealed: the subjects and programs, tuition fees, help to poor but talented students (scholarships, etc.). It is shown that in the early 20th century the number of students in secondary education institutions increased, which led to the opening of new educational institutions in Katerinoslav Province. The quantitative composition of students in different years in male and female educational institutions of that period and their social strata are characterized. It is shown that not only state secondary education institutions were opened, but also private ones. Characteristic of this period was the creation of various public organizations that took care of the development of education. Philanthropy in the sphere of education among the local elite and business community reached a significant scale. Thus, it is proved that the reform of the secondary school, though it hasn’t not received legislative support in the Russian Empire, but it was put into practice, that led to the growth of the number of private educational institutions, as well as public and charitable initiatives related to the education of insolvent population. Coverage of the work of individual educational institutions during that period gives an opportunity to get an idea of the Russian government; s domestic policy concerning education, to draw conclusions about the level of literacy and education and the social structure of education.